HASIL BELAJAR MATERI KEHADIRAN ISLAM DI NUSANTARA DENGAN MENGGUNAKAN TEKNIK MIND MAPPING PADA SISWA KELAS 9.1 SMPN 6 BANDUNG - Neni Hasinah (Jurnal Literasi Pendidikan Dasar, 2023)
This study aims to improve learning outcomes using mind mapping techniques to help 9.1. students at SMPN 6 Bandung on the material Presence of Islam in the Archipelago, the subject of Islamic Religious Education. There were 30 students who participated in this classroom action research for two cycles. The first cycle teaches students about the presence of Islam in the archipelago using Mind Mapping, while the second cycle improves the first cycle after going through reflection. There were stages of preparation, implementation, evaluation, and review in each cycle. Tests, class observations, and student surveys all contribute to a body of information that is analyzed both numerically and subjectively. The results showed that Islamic Religious Education learning outcomes of 9.1. students at SMPN 6 Bandung increased drastically with the application of a mind mapping strategy. Thus, the mind mapping strategy for learning Islamic Religious Education can be well received by students.